2022
DOI: 10.35848/1347-4065/aca0fd
|View full text |Cite
|
Sign up to set email alerts
|

Ca silicide films—promising materials for silicon optoelectronics

Abstract: Single-phase films of semiconductor and semimetallic calcium silicides (Ca2Si, CaSi, and CaSi2), as well as films with a significant contribution of Ca5Si3 and Ca14Si19 silicides, were grown on single-crystal silicon and sapphire substrates. The analysis of the crystal structure of the grown films was carried out and the criterion of their matching with silicon and sapphire substrates was determined. Some lattice matching models were proposed, and the subsequent deformations of the silicide lattices were estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 64 publications
0
0
0
Order By: Relevance
“…Orthorhombic Ca 2 Si is semiconductive with a direct energy bandgap of about 0.88 eV, recently reported from optical spectra of a Ca 2 Si thin film on sapphire substrate [32], which is slightly lower than the value of 1.02 eV found with GW calculations, a post-DFT method that corrects the energy bandgap obtained from the DFT method [40]. Growth of thin films has been performed for applications such as light-emitting diodes in the near-infrared range [32]. Thermoelectric and electrical transport experiments on orthorhombic Ca 2 Si [43,44] showed that it is p-type and that the electrical conductivity (σ) is too weak, even after doping with Na, and that the energy activation found is much smaller than the energy bandgap found from the optical experiments [32].…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…Orthorhombic Ca 2 Si is semiconductive with a direct energy bandgap of about 0.88 eV, recently reported from optical spectra of a Ca 2 Si thin film on sapphire substrate [32], which is slightly lower than the value of 1.02 eV found with GW calculations, a post-DFT method that corrects the energy bandgap obtained from the DFT method [40]. Growth of thin films has been performed for applications such as light-emitting diodes in the near-infrared range [32]. Thermoelectric and electrical transport experiments on orthorhombic Ca 2 Si [43,44] showed that it is p-type and that the electrical conductivity (σ) is too weak, even after doping with Na, and that the energy activation found is much smaller than the energy bandgap found from the optical experiments [32].…”
Section: Introductionmentioning
confidence: 81%
“…Among all the other calcium silicide compounds, density functional theory (DFT) calculations show that only Ca 2 Si, Ca 3 Si 4 , and Ca 14 Si 19 are semiconducting compounds [28,[39][40][41][42]. Orthorhombic Ca 2 Si is semiconductive with a direct energy bandgap of about 0.88 eV, recently reported from optical spectra of a Ca 2 Si thin film on sapphire substrate [32], which is slightly lower than the value of 1.02 eV found with GW calculations, a post-DFT method that corrects the energy bandgap obtained from the DFT method [40]. Growth of thin films has been performed for applications such as light-emitting diodes in the near-infrared range [32].…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations